Upgrading Pengurus BPRS Anggota Asbisindo Jawa Timur Plus Melalui Pelatihan Manfaat Penerapan Teknologi Informasi - Tatik Prihatini; Mochamad Fatchurrohman; Shobikin (Jurnal Hilirisasi Pengabdian Masyarakat, 2024)
The use of information technology in Islamic Rural Banks (BPRS) is still a challenge in itself, especially because of differences in understanding regarding the benefits and need for information technology among BPRS administrators. This lack of understanding often hinders the implementation and adoption of information technology. Several main administrators reject changes made in the field of information technology due to a lack of knowledge about the advantages and benefits to be obtained. Based on this description, this community service aims to improve the understanding of BPRS administrators about the benefits of adopting information technology to improve BPRS performance. In collaboration with Asbisindo, namely the East Java Plus branch of the BPRS association, community service is carried out through socialization to BPRS administrators not only at the main director level but also at other administrator levels including: commissioners, operational directors and at the level of section heads as parties involved in deciding the adoption of information technology. The research method for this community service uses a descriptive qualitative method. The results of this community service research are socialization at all levels of administrators, not only at the director level, which is able to bridge the gap in knowledge and communication in the process of adopting information technology at BPRS. By involving administrators, the adoption of information technology at BPRS can be carried out more effectively, so that the performance and operational efficiency of BPRS can increase as a whole